Public knowledge and stigma of autism spectrum disorder: Comparing China with the United States. (August 2020) - Yu, Luodi; Stronach, Sheri; Harrison, Ashley J
Autism spectrum disorder in China differs considerably from autism spectrum disorder in the West in terms of prevalence estimates, education opportunities, and life outcomes of autistic people. The lack of autism spectrum disorder awareness could be a key factor underlying the disparities. To date, there has been no evaluation of autism spectrum disorder knowledge among the general public of China. Using the Autism Stigma and Knowledge Questionnaire developed for use in diverse cultural contexts, this study uncovered profoundly different public views about autism spectrum disorder in China compared with the United States. Determined by cognitive diagnosis modeling, 86%–91% of the surveyed U.S. citizens ( N = 1127) achieved adequate autism spectrum disorder knowledge in diagnosis/symptoms, etiology, and treatment, whereas for the Chinese citizens ( N = 1254) the percentages were only 57%–65%. Moreover, 14% of the participants from the United States were classified to endorse autism spectrum disorder stigma; in comparison, 38% of the Chinese participants endorsed autism spectrum disorder stigma. The Chinese citizens displayed knowledge deficits primarily in the areas of autism spectrum disorder core symptoms, comorbid intellectual impairment, and prognosis. Sociodemographic factors associated with the Chinese citizen's misconceptions included gender, ethnicity, social economic factors, among others. These results have important implications for increasing public awareness and promoting community participation for autistic individuals in China. Lay abstract ASD in China differs considerably from ASD in the West in terms of prevalence estimates, education opportunities and life outcomes of autistic people. The lack of ASD awareness could be a key factor underlying these disparities. We asked 1127 U.S. citizens and 1254 Chinese citizens about their autism knowledge using the Autism Stigma and Knowledge Questionnaire (ASK-Q).The results indicated profoundly different public views about ASD in China compared to the U.S. Specifically, only 57%-65% of the Chinese citizens demonstrated adequate ASD knowledge compared to 86%-91% in the U.S. citizens. Fourteen percent of the U.S. citizens were shown to hold stigma beliefs towards ASD; in comparison, 38% of the Chinese citizens indicated ASD stigma. The Chinese citizens displayed misconceptions about ASD related to symptoms, causes, and possible long-term outcomes. In China but not in the U.S., male citizens and citizens with lower social economic status were more likely to have misconceptions about ASD than others were. The findings of this research can help increase public awareness about ASD and create a more inclusive environment for autistic people in China.